DUKUNGAN SOSIAL DAN KECEMASAN PADA PASIEN DIABETES MELITUS - Jauhari, Jauhari (Universitas Muhammadiyah Jember, 2016)
Patients with diabetes mellitus may arise anxiety that needs treatment in a comprehensive physical, psychological and social. Social support can affect the psychological anxiety by regulating the process. The purpose of research was analyze the relationship between social support and the level of anxiety in patients with diabetes mellitus. Croos sectional study design used by the respondents as many as 30 patients with purposive sampling technique. Data was collected by using a questionnaire DSKS and KMKS. The results showed that nearly half of respondents have a social support in both categories by 40% and the level of anxiety in the category was 56.7%. Based on the test results of Spearman's correlation p value = 0.000, r = 0.737, which means there was a strong relationship between social support and anxiety in patients with diabetes mellitus. Social support involves emotions and a positive assessment on the individual in the face of the problem. This support is very influential for individuals to adapt and interact with their environment. Social support can be obtained from family members, friends, relatives and caregivers who are external sources that can provide relief to the patient in dealing with and facing an issue especially concerning the illness.